Quantifying Molecular Dynamics within Complex Cellular Morphologies using LLSM‐FRAP. Issue 6 (28th March 2022) - Colin‐York, Huw; Heddleston, John; Wait, Eric; Karedla, Narain; deSantis, Michael; Khuon, Satya; Chew, Teng‐Leong; Sbalzarini, Ivo F.; Fritzsche, Marco
Abstract: Quantifying molecular dynamics within the context of complex cellular morphologies is essential toward understanding the inner workings and function of cells. Fluorescence recovery after photobleaching (FRAP) is one of the most broadly applied techniques to measure the reaction diffusion dynamics of molecules in living cells. FRAP measurements typically restrict themselves to single‐plane image acquisition within a subcellular‐sized region of interest due to the limited temporal resolution and undesirable photobleaching induced by 3D fluorescence confocal or widefield microscopy. Here, an experimental and computational pipeline combining lattice light sheet microscopy, FRAP, and numerical simulations, offering rapid and minimally invasive quantification of molecular dynamics with respect to 3D cell morphology is presented. Having the opportunity to accurately measure and interpret the dynamics of molecules in 3D with respect to cell morphology has the potential to reveal unprecedented insights into the function of living cells. Abstract : Bio‐molecules continuously undergo reaction and diffusion dynamics within the complex spatial environment of the living cell. Using a combination of rapid volumetric lattice light sheet microscopy and fluorescence recovery after photobleaching, the proposed method addresses the need for tools that allow for the quantification of molecular dynamics in 3D cell morphologies.